Participatory Youth Budgets: a Contribution to the Debate of the Pedagogical Effects of Citizen Participation - González Salcedo, Antonia; Mayor Balsas, José Manuel (Revista del CLAD Reforma y Democracia, 2020)
Although in the field of political science considerable research has been done on the impact that the educational variable has on the political behavior of individuals, there has been much less attention on the educational impact of participatory processes. In recent decades, some research has been carried out confirming the acquired learning in participatory mechanisms developed at the local level, especially in the development of deliberative skills, democratic attitudes and political effectiveness. Some of these investigations has shown, in particular, the learnings of participants from participatory budgets. This work aims, precisely, to contribute with its results to confirm that mechanisms such as youth participatory budgets have a pedagogical dimension and contribute to the configuration of a better citizenship.
Keywords: Citizen Participation; Participatory Budgeting; Youth; Apprenticeship; Municipalities; Case Analysis; Spain